Relationship between Islamic bank consumptive financing and gross regional domestic product in Indonesia, 2016-2020 - Cinantya Sriyono Putri; Sri Herianingrum; Rifka Putri Ramadhanty; Nanda Lismatiara Zubaid; Yan Putra Timur (Department of Islamic Economics, Islamic University of Indonesia, 2023)
IntroductionPrevious literature discussed financing's impact on performance without separating the financing model.ObjectivesThis study uses the consumptive financing data of Islamic commercial banks, inflation rate, and population as independent variables, and the GRDP of 33 provinces in Indonesia as the dependent variable. MethodThe study used Indonesia and Malaysia banks for its pioneering efforts in establishing Islamic banking in Southeast Asia. The study collects data from five Indonesian and four Malaysian Islamic banks, with an observation period of 2011–2020. The data analysis used in this study was the Generalized Method of Moment (GMM).ResultsThe results of this study explain that the consumptive financing of Islamic commercial banks has a negative insignificant effect on GRDP in Indonesia, the inflation rate has a negative insignificant effect on GRDP in Indonesia, and the population has a positive and significant impact on GRDP in Indonesia. Consumptive credit in conventional banks and consumptive financing in Islamic banks account for more than 45% of total financing. ImplicationsThe Indonesian Financial Services Authority should adopt policies to maintain the growth of Islamic Bank productive financing, that is, working capital and investment financing, because Islamic bank consumptive financing has a negative effect on GRDP in IndonesiaOriginality/NoveltyThis study has a unique feature compared with previous studies that use consumptive financing at Islamic banks with inflation and population variables to analyze the contribution of the local economy to gross regional domestic product.